Pemanfaatan Koleksi Buku Sebagai Penunjang Tugas Akhir Mahasiswa Program Studi Tafsir dan Hadis UIN Sayyid Ali Rahmatullah Tulungagung - Hariyati, Henik; Prajawinanti, Arin (Universitas Negeri Padang, 2024)
This research focuses on the utilization of book collections by senior students in the Tafsir and Hadith studies program as references for their thesis. The study aims to reveal the understanding of senior students in utilizing book collections as reference sources, employing a qualitative approach with interview and descriptive case study methods. Participants in the study were selected using purposive sampling from senior students in the mentioned program. Data were collected through interviews, observations, and literature reviews, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that students consider book collections as essential reading materials and sources of knowledge to support their thesis writing. Identified challenges include the limited and outdated nature of book collections, students' lack of awareness regarding the location of required collections, librarian services, and retrieval facilities. Therefore, it is recommended to make efforts to improve the availability and accessibility of book collections, as well as enhance students' understanding of utilizing informational resources in the library.